Analysis of Bearing Capacity and Seismic Performance of Circular RC Columns Strengthened with Externally Wrapped Steel Plates - Chunli Zhou; Xiaowei Li; Dongbo Wang; Shunxiang Xia (Advances in Civil Engineering)
Based on a practical project, the construction method of circular reinforced concrete (RC) columns strengthened with externally wrapped steel plates was introduced in this paper. In order to study the bearing capacity and seismic performance of circular RC columns after strengthening, a formula for calculating the bearing capacity of circular RC columns strengthened with externally wrapped steel plates was derived, with reference to the Code for Design of Strengthening Concrete Structure. Through ABAQUS software, the vertical monotone static loading analysis and the horizontal low-cyclic reversed loading analysis were carried out, respectively, before and after the strengthening of the full-size RC columns in this project. The results showed that the bearing capacity of the normal section of the RC column after strengthening was about 80% higher than that before strengthening, and the results of FEM software were in accord with the calculation results of theoretical formula to some degree. Under horizontal low-cyclic reversed loading, the columns after strengthening had both plumper hysteresis curves and higher ductility factors and equivalent viscous damping coefficient than those before strengthening, indicating the energy dissipation capacity, plastic deformation capacity, and seismic performance of the RC columns after strengthening were all obviously improved.